Kānsưksā ph̄ưa kamnot rūpb̄æp kānth̨̄ongthīeo ch̄œng niwēt thāng thalē = Marine ecotourism (Sathāban Wičhai Witthayāsāt læ Thēknōlōyī h̄æng Prathēt Thai, 1998)
Study on various aspects of marine ecotourism in sample areas of Trat Province, Thailand.